Leveraging social protection to strengthen women’s and girls’ roles in climate-resilient agrifood systems - Hidrobo, Melissa; Mueller, Valerie; Bryan, Elizabeth; Nesbitt-Ahmed, Zahrah; Läderach, Peter; Roy, Shalini (CGIAR, 2024)
Women and girls (WGs) have important roles in making agrifood systems more climate-resilient. However, systematic inequalities in access to resources, technologies, information, services, and networks reduce their capacity to adapt to and mitigate climate change – with implications for the wellbeing of WGs and their households and the sustainability of agrifood systems. With growing recognition that social protection helps promote WGs’ resilience in low- and middle-income countries (LMICs) at large scale, stakeholders are interested in developing social protection programs that are responsive to both climate change and gender inequality. However, little is known about effective approaches. We reflect on emerging evidence on how social assistance –the most prevalent type of social protection programming in many LMICs – affects WGs’ coping, adaptive, and mitigative responses to climate hazards. Drawing on this evidence, we propose recommendations on program design features that may more effectively promote WGs’ roles in climate-resilient agrifood systems. We additionally highlight important directions for future research to guide practice.